El realismo pragmático en la concepción habermasiana de la verdad - Candioti, María Elena (ARFIL y UNL, 2018)
In Wahrheit und Kechtfertigung Habermas presents a re-elaboration of the idea of truth, in which he points out the shortage of a conception within the limits set by a discursive framework and brings up his intention of articulating the pragmatic- transcendental perspective to a weakened conception of naturalism. The article analyzes the scope of the Kant-based “pragmatic realism” with which Habermas intends to reinforce the differences with the contextualized positions, giving predominance to the processes of correction and adjustment. In this sense, H. Putnam’s incidence on Habermas’ thought is taken into consideration, especially concerning a conception of language which allows for the restitution of its referential function, and a new comprehension of experience as linguistically mediated. Finally, a revision is presented of the implications of this idea of truth, in the cognitive field as much as in that of practical discourse, and of the way in which the relations between truth and justice come up in the framework of this issue.